Enzyme Activity and De Ritis Ratio in Alcoholic and Non Alcoholic Fatty Liver Patients based on Ultrasonography - Rawal, Sanju; Shahi, Aakash; Gautam, Narayan; Jayan, Archana; Sharma, Uday (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Fatty liver disease (FLD) refers to a wide clinical and histological spectrum from simple hepatic steatosis to steatohepatitis or cirrhosis, and FLD has been classiﬁed as nonalcoholic FLD (NAFLD) and alcoholic FLD (AFLD) based on etiology and ultrasonography (USG). MATERIAL AND METHODS: This Cross-sectional study was undertaken in the Department of Radiology, Universal College of Medical Sciences (UCMS), Bhairahawa, Nepal from March 2019 to February 2020. A total of 100 subjects involved where ultrasonographically graded for fatty liver and enzyme activity were assessed to observe their association. RESULTS: In 100 cases, 66% were male and 34% were female. Ultrasonography (USG) guided FLD grade 1 patients were 81%, FLD grade 2 patients were 19% where as no cases was observed for FLD grade 3. Fifty Six percent (56%) of the total cases presented with AFLD while remaining 44% with NAFLD. There was significant difference in serum glutamate oxaloacetate transaminase (SGOT) (p-value: 0.003), serum glutamate pyruvate transaminase (SGPT) (p-value: 0.011) and alkaline phosphatase (ALP) (p-value: 0.003) in AFLD and NAFLD. However, there was no significant association of enzyme activity with FLD grade (p-value >0.05). There was significant difference in SGOT (p-value: 0.004), SGPT (p- value: 0.025) between AFLD grade 1 (AFLDG1) and NFLD grade 1 (NAFLDG1), SGOT (p-value: 0.016) between AFLDG2 and NAFLDG2 and ALP (p-value: 0.01) between AFLDG1 and NAFLDG1. However, De Ritis ratio was not significantly associated with fatty liver disease. CONCLUSION: USG is a non-invasive simple tool for early detection of fatty liver in asymptomatic patients enabling clinicians to achieve early detection in conjunction with hepatic enzymes.